Characterization of functionalized multiwalled carbon nanotubes and comparison of their cellular toxicity between HEK 293 cells and zebra fish in vivo. Issue 10 (October 2019) - Chowdhry, Ayush; Kaur, Jasreen; Khatri, Madhu; Puri, Veena; Tuli, Rakesh; Puri, Sanjeev
Abstract: Carbon nanotubes (CNTs) hold tremendous potential due to their unique and modifiable properties. Their robust biological applications necessitate minimizing their cytotoxicity and increasing the solubilization. In the present manuscript, we have functionalized multiwalled carbon nanotubes (MWCNTs) using defect functionalization methodology to covalently bind carboxy and amino groups on their walls. This functionalization was reassured through fourier-transform infrared spectroscopy (FTIR), energy dispersive x-ray analysis (EDX), elemental and field emission scanning electron microscopy (FE-SEM) analysis. The observations demonstrated that addition of carboxy as well as amino groups on MWCNTs, besides enabling MWCNTs solubilization also significantly ameliorated the cytotoxicity and the oxidative stress in comparison to pristine MWCNTs. It is envisaged that changes in agglomeration of the functionalized MWCNTs and the acquired surface charge is the reason for the reduction of cytotoxicity. Zebra fish embryo model test system employed for in vivo analysis of the MWCNTs showed no significant toxicity on account of any nanoparticle tested pointing towards intrinsic mechanisms in place for deterring the damage in complex organisms. Overall, the observations besides pointing towards functionalized MWCNTs effectiveness towards weakening the toxicity of pristine MWCNTs also caution for extrapolating in vitro data to in vivo observations. The observations further lend credibility for exploiting the zebra fish as a model system for analyzing the effects of MWCNTs functionalization. Abstract : Materials science; Chemistry; Environmental science; Biological sciences; Carbon nanotubes (CNTs); Multi walled carbon nanotubes (MWCNTs); Functionalized MWCNTs; MWCNT cytotoxicity